Management of abnormal uterine bleeding – focus on ambulatory hysteroscopy - Kolhe S (Dove Medical Press, 2018)
Shilpa Kolhe Ambulatory Gynaecology Unit, Royal Derby Hospital, Derby, UK Abstract: The rapid evolution in ambulatory hysteroscopy (AH) has transformed the approach to diagnose and manage abnormal uterine bleeding (AUB). The medical management in primary care remains the mainstay for initial treatment of this common presentation; however, many women are referred to secondary care for further evaluation. To confirm the diagnosis of suspected intrauterine pathology, the traditional diagnostic tool of day case hysteroscopy and dilatation and curettage in a hospital setting under general anesthesia is now no longer required. The combination of ultrasound diagnostics and modern AH now allows thorough evaluation of uterine cavity in an outpatient setting. Advent of miniature hysteroscopic operative systems has revolutionized the ways in which clinicians can not only diagnose but also treat menstrual disorders such as heavy menstrual bleeding, intermenstrual bleeding and postmenopausal bleeding in most women predominantly in a one-stop clinic. This review discussed the approach to manage women presenting with AUB with a focus on the role of AH in the diagnosis and treatment of this common condition in an outpatient setting. Keywords: abnormal uterine bleeding, ambulatory hysteroscopy, endometrial polyps, one-stop clinic, vaginoscopic approach